A design approach of the solar harvesting control system for wireless sensor node. (November 2015) - Frezzetti, Antonio; Manfredi, Sabato; Pagano, Mario
Abstract: In the last recent years the implementation of PV (PhotoVoltaic) solar harvesting maximum power point tracking (MPPT) systems has been widely investigated to achieve self-powered and fully autonomous wireless sensor networks (WSNs). In this context, this paper mainly aims to design an efficient and long-lived solar harvesting control system for sensor nodes. Specifically, a design approach of the overall solar harvesting control system, that is composed of PV source, controller, converter, and UltraCapacitor (UC), is provided in order to obtain the desired performance in terms of autonomy and efficiency. The methodology is based on the analytical derivation of system efficiency and takes into account design requirements. The approach is applied to the design of an harvesting control system supplying an off-the-shelf Texas Instruments eZ 430 − RF 4500 mote. The prototype is realized and used to experimentally validate the approach by mean of out-door four days test. The experimental results show the effectiveness of the methodology to assess the required performance in terms of efficiency (about 0.86) and autonomy (four days). Abstract : Highlights: A systematic procedure aimed to design harvesting Control system is provided. Performance in terms of system efficiency and autonomy are considered. The approach can be applied to the design of off-the-shelf system components. The effectiveness of the approach is confirmed by experimental results.